Grammar and communication in portuguese as a foreign language: A study in the context ofteletandem interactions - Consolo, Douglas Altamiro [UNESP] (2009)
This paper presents a study about the role of grammar in on-line interactions conducted in Portuguese and in English, between Brazilian and English-speaking interactants, with the aim of teaching Portuguese as a foreign language (PFL). The interactions occurred by means of chat and the MSN Messenger, and generated audio and video data for language analysis. Grammar is dealt with from two perspectives, an inductive and a deductive approach, so as to investigate the relevance of systematization of grammar rules in the process of learning PFL in teletandem interactions.